2017
DOI: 10.1386/ajms.6.3.463_1
|View full text |Cite
|
Sign up to set email alerts
|

Translation in the newsroom: Losing voices in multilingual newsflows

Abstract: The information, events and voices that receive media attention are highly dependent on their linguistic form – when the language is accessible to journalists, the news is more likely to enter public discourse. If the voices are in languages other than that of the region the journalist is writing for, then translation strategies can influence not only the news style but also the selection and perspectivation of the information presented. In this article, we discuss how working between languages inside the news… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Political issues regarding the presence of the other language in the news were not reported, unlike in other contexts: at the Canadian French-speaking broadcast Le Droit, the analysis of the presence of English by watchdog associations make the reporters fear complaints when they interview English-speaking respondents who are not perceived as essential to the story, compared to French-speaking alternatives (Gendron et al, 2019). This priority of intelligibility in the language of the broadcast confirms how journalists rather privilege domestication strategies (Perrin et al, 2017). Furthermore, when in Dutch, interviews at the RTBF are often voiceover translations, while interviews are systematically subtitled at the VRT.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Political issues regarding the presence of the other language in the news were not reported, unlike in other contexts: at the Canadian French-speaking broadcast Le Droit, the analysis of the presence of English by watchdog associations make the reporters fear complaints when they interview English-speaking respondents who are not perceived as essential to the story, compared to French-speaking alternatives (Gendron et al, 2019). This priority of intelligibility in the language of the broadcast confirms how journalists rather privilege domestication strategies (Perrin et al, 2017). Furthermore, when in Dutch, interviews at the RTBF are often voiceover translations, while interviews are systematically subtitled at the VRT.…”
Section: Discussionmentioning
confidence: 87%
“…Financial and logistical considerations explained this resistance, but cultural differences were also raised: some feared that translated news did not cover important topics in a way that was meaningful for the members of their language community (Conway, 2008). Perrin et al (2017) found that news events inciting a lot of media attention directly depend on the journalists' skills in the language in which the events unfold; if journalists do not understand that language, they are less likely to include the event in a broadcast. Within the Belgian context, however, Jacobs and Tobback (2013) argued that language itself does not determine whether a report is included in the TV news bulletin or not, but rather that it happens in the country's other linguistic communities.…”
Section: (Foreign) Language In Journalismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, they are nearly all in favour of subtitling, given the role they infer to TV dubbing in the Francophones' poor linguistic skills. Therefore, with subtitled instead of dubbed interviewees in news reports, the journalists in this study favour the "foreignization strategy" rather than the "domestication strategy" (Venuti 1995;Perrin et al 2017).…”
Section: Resultsmentioning
confidence: 94%
“…The language barrier is to be found on the politicians' side, who might see their participation in Flemish TV broadcasts as particularly face-threatening, and not from the journalists' side. In a more general way than in the context of elections, Perrin et al (2017) insist on the practical impact of the journalists' linguistic skills. Indeed, events that gain high media attention directly depend on the journalists' skills in the language in which the events are reported.…”
Section: Two Distinct Media Landscapesmentioning
confidence: 99%